2015
DOI: 10.1016/j.jqsrt.2015.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Cloud chamber laboratory investigations into scattering properties of hollow ice particles

Abstract: Copyright 2015 The Authors. Published by Elsevier Ltd.This is an open access article under the CC-BY license (http://creativecommons.org/licenses/by/4.0/). Date of Acceptance: 16/02/2015Measurements are presented of the phase function, P11, and asymmetry parameter, g, of five ice clouds created in a laboratory cloud chamber. At ???7 ??C, two clouds were created: one comprised entirely of solid columns, and one comprised entirely of hollow columns. Similarly at ???15 ??C, two clouds were created: one consisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 66 publications
2
18
0
Order By: Relevance
“…But at low supersaturations, the hollow often varies in width, getting wider, then getting narrower, and finally closing-off into a center pocket. Oscillations also occur at middling-to-high supersaturations (e.g., Smith et al, 2015), but are much more pronounced at the low supersaturations in our experiments here. Gonda and Koike (1983) also observed the closing-off of hollows during growth at one atmosphere and supersaturations up to 33% at −30 °C.…”
Section: Hollow Close-off To Center Pockets and Terracing 10supporting
confidence: 45%
See 1 more Smart Citation
“…But at low supersaturations, the hollow often varies in width, getting wider, then getting narrower, and finally closing-off into a center pocket. Oscillations also occur at middling-to-high supersaturations (e.g., Smith et al, 2015), but are much more pronounced at the low supersaturations in our experiments here. Gonda and Koike (1983) also observed the closing-off of hollows during growth at one atmosphere and supersaturations up to 33% at −30 °C.…”
Section: Hollow Close-off To Center Pockets and Terracing 10supporting
confidence: 45%
“…But ice and snow crystals usually have more complex shape features, such as hollows and branches, known as the secondary habit (e.g., Kikuchi et al, 2013). These features have recently attracted attention because the crystal "complexity" affects radiative scattering of ice-containing clouds (e.g., Smith et al, 2015;Järvinen et al, 2018). 25…”
Section: Normal Growth Primary Vs Secondary Habits and Interior Feamentioning
confidence: 99%
“…Laboratory and modeling studies have shown that the angular light scattering properties of randomly oriented complex ice particles strongly differ from those of pristine crystals (Ulanowski et al, 2006;Smith et al, 2015;Schnaiter et al, 2016;Baum et al, 2010;Baran, 2012). While pristine hexagonal ice crystals show the 22 and 46 • halo features as well as the ice bow feature at scattering angles between about 135 and 160 • , the angular light scattering of complex crystals is characterized by a flat and featureless function with larger scattering cross sections for side and backscattering directions.…”
Section: Introductionmentioning
confidence: 99%
“…11a and 13a). The shift of the halo peak towards larger angles than the 22 • shown by the more familiar single-scattering SPF computed from geometric optics can be interpreted as originating from the combined contributions from background sky scattering, diffraction effects (due to small crystal size) and crystal roughness (Macke et al, 1996;Ulanowski, 2005;Liu et al, 2013;Smith et al, 2015). The SPF was obtained by taking the mean of the three camera channels.…”
Section: Resultsmentioning
confidence: 99%